Arenavirus Z-glycoprotein association requires Z myristoylation but not functional RING or late domains - Capul, Althea A; Perez, Mar; Burke, Emily; Kunz, Stefan; Buchmeier, Michael J; de la Torre, Juan C (Journal of virology, 2007)
Generation of infectious arenavirus-like particles requires the virus RING finger Z protein and surface glycoprotein precursor (GPC) and the correct processing of GPC into GP1, GP2, and a stable signal peptide (SSP). Z is the driving force of arenavirus budding, whereas the GP complex (GPc), consisting of hetero-oligomers of SSP, GP1, and GP2, forms the viral envelope spikes that mediate receptor recognition and cell entry. Based on the roles played by Z and GP in the arenavirus life cycle, we hypothesized that Z and the GPc should interact in a manner required for virion formation. Here, using confocal microscopy and coimmunoprecipitation assays, we provide evidence for subcellular colocalization and biochemical interaction, respectively, of Z and the GPc. Our results from mutation-function analysis reveal that Z myristoylation, but not the Z late (L) or RING domain, is required for Z-GPc interaction. Moreover, Z interacted directly with SSP in the absence of other components of the GPc. We obtained similar results with Z and GPC from the prototypical arenavirus lymphocytic choriomeningitis virus and the hemorrhagic fever arenavirus Lassa fever virus.